Exosome-mediated RNAi of PAK4 prolongs survival of pancreatic cancer mouse model after loco-regional treatment. (January 2021) - Xu, Lizhou; Faruqu, Farid N.; Lim, Yau M.; Lim, Kee Y.; Liam-Or, Revadee; Walters, Adam A.; Lavender, Paul; Fear, David; Wells, Claire M.; Tzu-Wen Wang, Julie; Al-Jamal, Khuloud T.
Abstract: With a dismal survival rate, pancreatic cancer (PC) remains one of the most aggressive and devastating malignancies, predominantly due to the absence of a valid biomarker for diagnosis and limited therapeutic options for advanced diseases. Exosomes (Exo) as cell-derived vesicles, are widely used as natural nanocarriers for drug delivery. P21-activated kinase 4 (PAK4) is oncogenic when overexpressed, promoting cell survival, migration and anchorage-independent growth. Herein we validated PAK4 as a therapeutic target in an in vivo PC tumour mouse model using Exo-mediated RNAi following intra-tumoural administration. PC derived Exo were firstly isolated by ultracentrifugation on sucrose cushion and characterised for their surface marker expression, size, number, purity and morphology. SiRNA was encapsulated into Exo via electroporation and dual uptake of Exo and siRNA was investigated by flow cytometry and confocal microscopy. In vitro siPAK4 silencing in PC cells following uptake was assessed by flow cytometry, western blotting, and in vitro scratch assay. In vivo efficacy (tumour growth delay and mouse survival) of siPAK4 was evaluated in PC bearing NSG mouse model. Ex vivo tumours were examined using Haematoxylin and eosin (H&E) staining and immunohistochemistry. Results showed high quality PC-derived PANC-1 Exo were obtained. SiRNA was incorporated in Exo with 16.5% encapsulation efficiency. In vitro imaging confirmed Exo and siRNA co-localisation in cells. PAK4 knockdown was successful with 30 nM Exo-siPAK4 at 24 h post incubation in vitro . Intra-tumoural administration of Exo-siPAK4 (0.03 mg/kg siPAK4 and 6.1 × 10 11 Exo, each dose, two doses) reduced PC tumour growth in vivo and enhanced mice survival (p < 0.001), with minimal toxicity observed compared to polyethylenimine (PEI) used as a commercial transfection reagent. H&E staining of tumours showed significant tissue apoptosis in siPAK4 treated groups. PAK4 knockdown prolongs survival of PC-bearing mice suggesting its potential as a new therapeutic target for PC. PANC-1 Exo demonstrated comparable efficacy but safer profile than PEI as in vivo RNAi transfection reagent. Graphical abstract: Image 1